∫ − 2 2 tan − 1 ( e sin x ) d x
The integral above has a closed form. Find the value of this closed form.
Give your answer to 2 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using properties of Definite Integrals, ∫ − a a f ( x ) d x = ∫ 0 a f ( x ) + f ( − x ) d x
So I = ∫ 0 2 arctan ( e sin x ) + arctan ( e sin ( − x ) ) d x = ∫ 0 2 arctan ( e sin x ) + arctan ( e sin x 1 ) d x
Now since e sin x > 0 for all real values of x , arctan x 1 = a r c c o t x = 2 π − arctan x
So, I becomes I = ∫ 0 2 arctan ( e sin x ) + 2 π − arctan ( e sin x ) d x = ∫ 0 2 2 π d x = π
When manipulating such integrals, you also have to be careful that we do not have an ∞ − ∞ scenario. This can be justified by placing appropriate bounds on arctan e sin x .
FYI Typo in the equation
arctan x 1 = a r c c o t x = 2 π − arctan x
Can anyone explain the Challenge master note, please ?
Log in to reply
As an explicit example, ∫ − 1 1 x 1 d x is undefined. (If you disagree, review how such integrals are defined when we get close to a value at infinity.)
However, if you used this method, you would claim that the answer is 0.
I used integration by parts.
Let u = a r c t a n ( e s i n x ) , d v = d x
Then,
d x d u = 1 + e 2 s i n x e s i n x c o s x , v = x
The integral then becomes,
∫ − 2 2 a r c t a n ( e s i n x ) d x = x a r c t a n ( e s i n x ) ∣ ∣ ∣ ∣ − 2 2 − ∫ − 2 2 1 + e 2 s i n x x e s i n x c o s x d x
The function in the second integral is odd, which we can prove by plugging in some -x. So the integral itself is zero. This means,
∫ − 2 2 a r c t a n ( e s i n x ) d x = x a r c t a n ( e s i n x ) ∣ ∣ ∣ ∣ − 2 2
This is equal to π
Log in to reply
Okay. Why don't you go ahead and post it as a solution?
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Integration Tricks
First note: tan − 1 ( e sin x ) = cot − 1 ( e − sin x ) = 2 π − tan − 1 ( e − sin x ) Next, denote the integral by R and apply ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x and add the two to get:
2 R = ∫ − 2 2 ( tan − 1 ( e − sin x ) + tan − 1 ( e sin x ) ) d x
= ∫ − 2 2 ( tan − 1 ( e − sin x ) + 2 π − tan − 1 ( e − sin x ) ) d x
= ∫ − 2 2 2 π d x = 2 π
∴ R = π ≈ 3 . 1 4